Translating English-Indonesia Authentic Text Entitled OSAKA - Sanur, Fransiskus (Lingual Journal of Language and Culture, 2017)
This paper aims to identify and describe the procedures of translation of  Osaka  in Garuda Magazine, the translation strategies employed, and how to find out the form and the occurrence of seven procedures of translation which proposed by Vinay and Darbelnet in 1995. Seven types of translation procedures have been identified and can be further categorized into two methods of translation, namely direct or literal translation and oblique translation. The result of data analysis shows that some of the procedure proposed by Vinay and Darberlnet occurs. Most of the data are translated using translation procedures, which are borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. Keywords: direct or literal translation and oblique translation, Translation Procedures